Hubungan kadar fluoride air tanah dengan kejadian karies gigi pada anak di Wilayah Pesisir Kota Kupang - Simamora, Friska Delianti; Sidabutar, Manginar; Ratu, Antonius R. (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Fluoride is an inorganic element that plays a crucial role in dental health through drinking water. Variations in groundwater fluoride levels in coastal areas can affect dental health, especially dental caries. The optimal fluoride concentration to prevent caries is 0,7 mg/L, with a maximum limit of 1,5 mg/L according to Ministry of Health Regulation No. 32 of 2017.Objective: This study aimed to determine the fluoride concentration in coastal groundwater and its association with dental caries incidence in children.Methods: An analytical observational cross-sectional study was conducted using simple random sampling on 26 children aged ≥2 years residing in coastal areas who used groundwater as their drinking water source. The study was carried out in Oesapa Village, Kupang City, in May 2024. Data were collected using questionnaires and dental caries examinations with the DMF-T index. Data were analyzed using correlation tests between fluoride levels and caries incidence.Results: Groundwater fluoride levels ranged from 0,00 to 1,01 mg/L (mean 0,28 mg/L), remaining below the safe limit of 1,5 mg/L. The mean dmf-t score for primary teeth was 2,36, and the DMF-T score for permanent teeth was 0,08, indicating generally good dental status among children. Statistical analysis showed no significant correlation between fluoride concentration and caries incidence (p= 0,796). Behavioral factors such as tooth brushing habits and sugar consumption were suspected to influence caries occurrence.Conclusions: Fluoride levels in coastal groundwater of Oesapa were within normal limits and met Ministry of Health standards. Caries incidence was low, and no association was found between fluoride levels and caries prevalence.